All AlGaN epitaxial structure solar-blind avalanche photodiodes with high efficiency and high gain. (13th April 2016) - Wu, Hualong; Wu, Weicong; Zhang, Hongxian; Chen, Yingda; Wu, Zhisheng; Wang, Gang; Jiang, Hao
Abstract: Solar-blind avalanche photodiodes were fabricated with an all AlGaN-based epitaxial structure on sapphire by metal–organic chemical vapor deposition. The devices demonstrate a maximum responsivity of 114.1 mA/W at 278 nm and zero bias, corresponding to an external quantum efficiency (EQE) of 52.7%. The EQE improves to 64.8% under a bias of −10 V. Avalanche gain higher than 2 × 10 4 was obtained at a bias of −140 V. The high performance is attributed to the all AlGaN-based p–i–n structure comprised of undoped and Si-doped n-type Al0.4 Ga0.6 N on a high quality AlN layer and highly conductive p-type AlGaN grown with In-surfactant-assisted Mg-delta doping.